Hubungan Antara Penguasaan Kosakata Dan Motivasi Membaca Dengan Kemampuan Menulis Eksposisi(Penelitian di SMA Negeri 1 Jogonalan Kabupaten Klaten) - Suyadi, Suyadi, Prof. Dr. Markhamah, M.Hum, Dr. Yakub Nasucha, M.Hum (2014)
Most high school students still have the ability and skill level is very low writing exposition. The purpose of this study was to determine the relationship between vocabulary and reading motivation with the ability to write exposition Jogonalan Klaten high school students, either simultaneously or partially. This research is descriptive research with quantitative approach. This study also categorized as correlational studies (correlational Research). The population in this study were all high school students Jogonalan Klaten Class XI 2013/2014 academic year as many as 258 students. The sample in this study was determined by using a random sampling method. Data Collection Techniques done with the vocabulary test, test the ability to write exposition, motivation measurement scale reading. Data analysis techniques using Multiple Linear Regression, t test, and the test f. The results showed that the mastery of vocabulary and reading motivation has been associated with the ability to write exposition either alone (partial) or jointly (simultaneously). When viewed from the size of contribution values to the independent variables on the dependent variable is the Standard Coefficient values (Table 4.8), it appears that the value of mastery vocabulary (0.622) is greater than the value of reading motivation (0.304). Thus the mastery vocabulary is a more dominant factor associated with the ability to write exposition rather than factors reading motivation. Suggestion from researchers is the teacher should provide training or duty and motivation which can enhance the ability to write exposition. Given the large effect of mastery vocabulary on the increase in the students' ability to write exposition should optimizing the school library's role in providing reading materials, which supports the library environment, as well as provide convenience in visiting hours at the library.